Biological autoluminescence for assessing oxidative processes in yeast cell cultures - Vahalová, Petra; Červinková, Kateřina; Cifra, Michal (Scientific reports, 2021)
Nowadays, modern medicine is looking for new, more gentle, and more efficient diagnostic methods. A pathological state of an organism is often closely connected with increased amount of reactive oxygen species. They can react with biomolecules and subsequent reactions can lead to very low endogenous light emission (biological autoluminescence-BAL). This phenomenon can be potentially used as a non-invasive and low-operational-cost tool for monitoring oxidative stress during diseases. To contribute to the understanding of the parameters affecting BAL, we analyzed the BAL from yeast Saccharomyces cerevisiae as a representative eukaryotic organism. The relationship between the BAL intensity and the amount of reactive oxygen species that originates as a result of the Fenton reaction as well as correlation between spontaneous BAL and selected physical and chemical parameters (pH, oxygen partial pressure, and cell concentration) during cell growth were established. Our results contribute to real-time non-invasive methodologies for monitoring oxidative processes in biomedicine and biotechnology.
Keywords: Saccharomyces cerevisiae; luminiscenční měření; Oxidation-Reduction; oxidace-redukce; reaktivní formy kyslíku; Luminescent Measurements; koncentrace vodíkových iontů; Reactive Oxygen Species; Hydrogen-Ion Concentration